2021
DOI: 10.1002/anie.202107947
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Intracrystalline Ionic Strength in MFI Zeolites on Aqueous Phase Dehydration of Methylcyclohexanols

Abstract: The impact of the concentration of hydrated hydronium ions and in turn of the local ionic strength in MFI zeolites has been investigated for the aqueous phase dehydration of 4‐methylcyclohexanol (E1 mechanism) and cis‐2‐methylcyclohexanol (E2 mechanism). The E2 pathway with the latter alcohol led to a 2.5‐fold higher activity. The catalytic activity normalized to the hydronium ions (turnover frequency, TOF) passed through a pronounced maximum, which is attributed to the increasing excess chemical potential of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…It was recently shown that the changed ionic strength and acid site density of MFI zeolites is responsible for a volcano-plot like change of the reaction rate of dehydration reactions. 31 Notably, it is stated that a H + (H 2 O) n complex with n = 8 sterically fills the pores of the MFI zeolites and that too close acid sites thus block each other for reactant access, leading to slower dehydration. An important but often ignored surface group is the silanol or Si(OH) group.…”
Section: +mentioning
confidence: 99%
“…It was recently shown that the changed ionic strength and acid site density of MFI zeolites is responsible for a volcano-plot like change of the reaction rate of dehydration reactions. 31 Notably, it is stated that a H + (H 2 O) n complex with n = 8 sterically fills the pores of the MFI zeolites and that too close acid sites thus block each other for reactant access, leading to slower dehydration. An important but often ignored surface group is the silanol or Si(OH) group.…”
Section: +mentioning
confidence: 99%
“…The mechanism of the dehydration of both cyclohexanol and methylcyclohexanols in zeolites was studied in-depth by Lercher's group, especially systemically considering the influence of intracrystalline ionic strength, solvent, Si/Al ratio of zeolites, water concentration, etc. 99,166–173 For the unimolecular cyclohexanol dehydration via the E1 mechanism in the gas phase, the cyclohexyl carbenium cation (C 6 H 11 + ) is formed by C–O bond cleavage of protonated cyclohexanol, and the calculated Bader charge of +0.93 | e | and stationary point on the free energy surface confirmed the existence of C 6 H 11 + as an intermediate (Fig. 16a and b).…”
Section: The Role Of Carbocations In Zeolite Catalytic Reactionsmentioning
confidence: 83%
“…Moreover, the density of cation-anion pairs can be determined based on the Si/Al radio of acidic zeolites, which further induces a high local ionic strength and increases the excess chemical potential of related organic reactants simultaneously. 166,169,171,173 The charged transition states are stabilized by cation-anion pairs, reducing the energy barrier and leading to higher reaction rates (Fig. 16d).…”
Section: Carbocations In Alcohol Dehydrationmentioning
confidence: 99%
See 1 more Smart Citation
“…4a) was closely related to the electron transfer process between proton of water and hydride of NaBH 4 as an electron donor by surface dark states even without the involvement of d 8 –d 10 group metals. Very recently, in the confined sub-nanopores of microporous zeolites, by 1 H NMR, Lercher's group captured similar H species, 77–85 which was called hydronium ions [H + (H 2 O) n ], but their formation was just simply attributed to the physical confinement of the nanocavity. The capturing of activated intermediate hydrogen species not only answered the origin of non-metal catalysts for hydride catalytic reductivity of 4-NP, 50,51 but also shed new light on the H + activation of water by non-metal catalysts in the electrocatalytic reactions.…”
Section: Resultsmentioning
confidence: 99%